Preparation method of composite wind power tower base mortar

Through the combination of plasma-modified composite cement and foamed spherical hole CaO·ZrO2, the problem of slow hardening of traditional seat mortar mortar in low temperature environment is solved, and the stable hardening and high compressive strength of wind power tower mortar under low temperature conditions is achieved, ensuring the stable operation of the wind power system.

CN118652091BActive Publication Date: 2025-03-07BEIJING ACAD OF BUILDING ENG
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410675900.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-29
Publication Date
2025-03-07
Estimated Expiration
2044-05-29

AI Technical Summary

Technical Problem

The condensation and hardening speed of traditional seat mortar mortar slows down in low temperature environments, resulting in the tower foundation being unable to withstand large loads in the early stages, affecting the stability of the wind power system, and decreasing fluidity and operability, affecting density and bonding performance.

Method used

Plasma modified composite cement and foamed spherical holes CaO·ZrO2 are used to treat the modified cement surface by plasma to increase its wettability and adhesion, and the porous structure of concrete is improved through foamed spherical holes CaO·ZrO2, thereby enhancing the compressive strength and stability after hardening.

Benefits of technology

Under low temperature conditions, the mortar of composite wind power tower seat can be stably and uniformly hardened, maintain a high compressive strength, improve the bearing capacity and stability of the tower foundation, and ensure the normal operation of the wind power system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118652091B_ABST
    Figure CN118652091B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of building materials, and more specifically to a method for preparing a composite wind power tower frame mortar. The method comprises the following steps: plasma modified composite cement; foamed spherical pore CaO·ZrO 2 Preparation of surface modified cement. The present invention is carried out by adding Ca(OAc) 2 and 2-3 parts by weight of Zr(NO 3 ) 4 ·5H 2 Preparation of CaO·ZrO 2 In the process of obtaining the gel, a foaming agent is added, ball milling and calcination are performed to obtain foamed spherical CaO·ZrO 2 , foamed spherical CaO·ZrO with porous structure 2 It can increase the surface contact area during the mixing process with surface modified cement to increase the bonding capacity, and provide a stable framework, so that when the sulphoaluminate cement undergoes hydration reaction to form calcium aluminate, it can better fill the gaps after the mortar hardens, maintain a stable hardened structure, and maintain a high compressive strength from the early to late stages of the mortar hardening.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a method for preparing composite wind power tower base mortar. Background Art

[0002] As a renewable energy source, wind power generation has been widely used and rapidly developed in recent years. As an important part of the wind power generation system, the structural stability and durability of the wind turbine tower directly affect the operating efficiency and safety of the wind turbine unit. During the installation of the wind turbine tower, the quality of the mortar plays a vital role in the bearing capacity and durability of the tower foundation.

[0003] Traditional mortar is usually composed of cement, sand and additives, which can provide good strength and bonding properties at room temperature. However, since cement generally uses low-cost silicate cement and sulfoaluminate cement, its coagulation and hardening speed in low temperature environment is significantly slowed down, making it difficult for the mortar to reach the designed strength in a short time. The tower foundation is difficult to withstand large loads in the early stages, which may cause settlement or displacement of the tower foundation and affect the stability of the entire wind power system. In addition, under low temperature conditions, the fluidity and operability of the mortar are significantly reduced, which will affect the uniformity and density of the mortar, and then affect the bonding performance and overall stability of the mortar. Summary of the invention

[0004] In order to solve the above technical defects, the present invention has developed a method for preparing a composite wind power tower base mortar which can ensure that the product hardens stably and evenly at low temperature and has excellent compressive strength.

[0005] A method for preparing a composite wind power tower base mortar comprises the following steps:

[0006] S1: Plasma modified composite cement

[0007] Mixing ultrafine silicate cement and sulphoaluminate cement in a mixer, adding a water retaining agent and a defoaming agent, stirring to obtain a mixed material, charging the mixed material into a closed mixer, starting a normal pressure plasma treatment machine to spray plasma gas into the closed mixer, performing plasma treatment while stirring, and obtaining surface modified cement;

[0008] S2: Preparation of foamed spherical CaO·ZrO2

[0009] Ca(OAc)2 and Zr(NO3)4·5H2O are dissolved in deionized water, and then anhydrous ethanol and a dispersant are added, and the mixture is heated in a constant temperature water bath after stirring, and filtered after centrifugation to obtain a gel precipitate, and ammonia water is slowly added dropwise to the gel precipitate while stirring, and the mixture is allowed to stand and then immersed in anhydrous ethanol for reflux, and washed to obtain a CaO·ZrO2 prepolymer, and the CaO·ZrO2 prepolymer is dried and ball-milled with a foaming agent, and then sintered to obtain foamed spherical porous CaO·ZrO2;

[0010] S3: Composite of surface modified cement

[0011] Surface modified cement and foamed spherical pore CaO·ZrO2 are sequentially added to quartz sand, stirred evenly to obtain a matrix mixture, fly ash, water reducing agent, antifreeze early strength agent, calcium carbonate stone powder and expansion agent are added to the matrix mixture, stirred evenly to obtain a composite wind power tower base mortar dry powder material, and when used, the composite wind power tower base mortar dry powder material is mixed with water to obtain a composite wind power tower base mortar for construction.

[0012] Furthermore, step S1 plasma modified composite cement comprises the following steps:

[0013] S1.1: 10-15 parts by weight of ultrafine silicate cement and 10-15 parts by weight of sulphoaluminate cement are mixed in a mixer, and then 0.02-0.03 parts by weight of a water retaining agent and 0.01-0.02 parts by weight of a defoaming agent are added, and stirred for 25-30 minutes to obtain a mixed material;

[0014] S1.2: Load the mixed material into a closed mixer, start the atmospheric pressure plasma treatment machine, adjust the working frequency to 20-25KHz, the voltage to 8-10kV, the voltage waveform to a sine wave, continuously spray the plasma gas from the nozzle into the closed mixer, and then start the mixer with a stirring speed of 100-120rpm for 2-3 hours to obtain surface modified cement.

[0015] Furthermore, the preparation of the foamed spherical CaO·ZrO2 in step S2 comprises the following steps:

[0016] S2.1: 2-3 parts by weight of Ca(OAc)2 and 2-3 parts by weight of Zr(NO3)4·5H2O are placed in a container, 6-8 parts by weight of deionized water are added, and the mixture is stirred until the solid matter in the container is completely dissolved. Then, 18-20 parts by weight of anhydrous ethanol and 0.3-0.4 parts by weight of a dispersant are added, and the mixture is stirred at a stirring speed of 240-300 rpm for 1.5-2 hours. The mixture is then placed in a constant temperature water bath and heated at a temperature of 75-80°C for 2-3 hours. The mixture is centrifuged and filtered to obtain a gel precipitate.

[0017] S2.2 Place the gel precipitate in a blender, slowly drop ammonia water while stirring at a stirring speed of 100-120 rpm, let it stand for 8-12 hours, then rinse it with deionized water until it is neutral, and then soak it in anhydrous ethanol, reflux for 1-1.5 hours, then take it out and wash it to obtain a CaO·ZrO2 prepolymer;

[0018] S2.3: Place the CaO·ZrO2 prepolymer in a vacuum drying oven and dry it at a temperature of 75-80℃ for 6-8 hours, then place it in a ball mill with 0.06-0.08 weight parts of foaming agent and ball mill it at a speed of 300-350rpm for 1-1.5 hours to obtain a CaO·ZrO2 foamed embryo, place the CaO·ZrO2 foamed embryo in a high-temperature sintering furnace and evacuate the pressure in the furnace to 100-600Pa, then introduce argon until the furnace returns to normal pressure, heat it to 800-1000℃ at a heating rate of 6-8℃ / min, keep it warm for 2-3 hours, then heat it to 1200-1400℃ at a heating rate of 10-15℃ / min, keep it warm for 3-4 hours, then cool it naturally to room temperature with the furnace to obtain foamed spherical pore CaO·ZrO2.

[0019] Furthermore, step S3 of compounding the surface-modified cement comprises the following steps:

[0020] S3.1: Add 20-30 parts by weight of surface-modified cement and 4-6 parts by weight of foamed spherical-pore CaO·ZrO2 to 15-20 parts by weight of quartz sand, stir evenly, and obtain a matrix mixture;

[0021] S3.2: Add 2-3 parts by weight of fly ash, 0.04-0.05 parts by weight of water reducing agent, 0.3-0.4 parts by weight of antifreeze early strength agent, 1-2 parts by weight of calcium carbonate stone powder and 2-3 parts by weight of expansion agent to the base mixture, stir evenly to obtain a composite wind power tower base mortar dry powder;

[0022] S3.3: When in use, mix the dry powder of the composite wind turbine tower base mortar with 10-14 parts of water to obtain the composite wind turbine tower base mortar for construction.

[0023] Furthermore, the water retaining agent in step S1.1 is hydroxypropyl methylcellulose, and the defoaming agent is tributyl phosphate.

[0024] Furthermore, the nozzle diameter in step S1.2 is 10-12 mm.

[0025] Furthermore, the dispersant in step S2.1 is polyethylene glycol.

[0026] Furthermore, in step S2.2, the ammonia water is added dropwise at a speed such that the pH value is 9-10 within 1-1.5 hours.

[0027] Furthermore, the foaming agent in step S2.3 is TiH2.

[0028] Furthermore, the water reducing agent in step S3.2 is a polycarboxylic acid powder water reducing agent, the antifreeze and early strength agent is calcium formate, and the expansion agent is a calcium sulfoaluminate expansion agent.

[0029] The beneficial effects are: 1. The present invention obtains foamed spherical pore CaO·ZrO2 by adding a foaming agent and performing ball milling and calcination during the process of preparing CaO·ZrO2 to obtain a gel by Ca(OAc)2 and 2-3 parts by weight of Zr(NO3)4·5H2O. The foamed spherical pore CaO·ZrO2 with a porous structure can increase the surface contact area during the mixing process with surface modified cement to increase the bonding ability, and provide a stable framework, so that when the sulphoaluminate cement undergoes hydration reaction to generate calcium aluminate, it can better fill the gaps in the composite wind tower base mortar after hardening, maintain a stable hardened structure, and enable the composite wind tower base mortar to maintain a high compressive strength from the early to late stages of hardening.

[0030] 2. The present invention improves the wettability and hydroxyl concentration of the substrate surface by mixed plasma treatment of ultrafine silicate cement, sulphoaluminate cement, water-retaining agent and defoaming agent. The oxygen ions in the plasma react with silicon-containing substances to form an easily bonded silicon dioxide layer, thereby enhancing the interfacial bonding strength between cement and the water-retaining agent and the defoaming agent, so that the water-retaining agent and the defoaming agent can better play the water-retaining and defoaming effects in the composite wind tower base mortar, so that it can have good water-retaining performance, and the composite wind tower base mortar has excellent initial fluidity, and the density of the base mortar is improved, and the compressive strength and hardening stability are further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The present invention is a flow chart of a method for preparing a composite wind power tower base mortar used in an embodiment of the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] A method for preparing a composite wind power tower base mortar, such as Figure 1 As shown, the following steps are included:

[0035] S1: Plasma modified composite cement

[0036] S1.1: 10 parts by weight of ultrafine silicate cement and 10 parts by weight of sulphoaluminate cement are mixed in a mixer, and then 0.02 parts by weight of hydroxypropyl methylcellulose and 0.01 parts by weight of tributyl phosphate are added, and stirred for 25 minutes to obtain a mixture;

[0037] S1.2: Load the mixed material into a closed mixer, start the atmospheric pressure plasma treatment machine, adjust the working frequency to 20KHz, the voltage to 8kV, the voltage waveform to a sine wave, and continuously spray the plasma gas into the closed mixer from the nozzle with a nozzle diameter of 10mm. Then start the mixer with a stirring speed of 100rpm for 2 hours to obtain surface modified cement.

[0038] S2: Preparation of foamed spherical CaO·ZrO2

[0039] S2.1: 2 parts by weight of Ca(OAc)2 and 2 parts by weight of Zr(NO3)4·5H2O are placed in a container, 6 parts by weight of deionized water are added, and the mixture is stirred until the solid matter in the container is completely dissolved. Then, 18 parts by weight of anhydrous ethanol and 0.3 parts by weight of polyethylene glycol are added, and the mixture is stirred at a stirring speed of 240 rpm for 1.5 hours. The mixture is then placed in a constant temperature water bath and heated at 75°C for 2 hours. The mixture is centrifuged and filtered to obtain a gel precipitate.

[0040] S2.2 Place the gel precipitate in a blender, slowly add ammonia water while stirring at a speed of 100 rpm, and add it within 1 hour to make the pH value 9. After standing for 8 hours, rinse it with deionized water until it is neutral, and then soak it in anhydrous ethanol. After refluxing for 1 hour, take it out and wash it to obtain CaO·ZrO2 prepolymer;

[0041] S2.3: Place the CaO·ZrO2 prepolymer in a vacuum drying oven and dry it at 75°C for 6 hours, then place it in a ball mill with 0.06 weight parts of TiH2 and ball mill it at 300rpm for 1 hour to obtain a CaO·ZrO2 foamed embryo. Place the CaO·ZrO2 foamed embryo in a high-temperature sintering furnace and evacuate the pressure in the furnace to 100Pa, then introduce argon until the pressure in the furnace returns to normal, heat it to 800°C at a heating rate of 6°C / min, keep it warm for 2 hours, then heat it to 1200°C at a heating rate of 10°C / min, keep it warm for 3 hours, then cool it naturally to room temperature with the furnace to obtain foamed spherical pore CaO·ZrO2.

[0042] S3: Composite of surface modified cement

[0043] S3.1: 20 parts by weight of surface-modified cement and 4 parts by weight of foamed spherical-pore CaO·ZrO2 are added to 15 parts by weight of quartz sand in sequence, and the mixture is stirred evenly to obtain a matrix mixture;

[0044] S3.2: Add 2 parts by weight of fly ash, 0.04 parts by weight of polycarboxylic acid powder water reducer, 0.3 parts by weight of calcium formate, 1 part by weight of calcium carbonate stone powder and 2 parts by weight of calcium sulphoaluminate expansion agent to the base mixture, stir evenly to obtain a composite wind power tower base mortar dry powder;

[0045] S3.3: When in use, mix the dry powder of the composite wind turbine tower base mortar with 10 parts of water to obtain the composite wind turbine tower base mortar for construction.

[0046] Example 2

[0047] A method for preparing a composite wind power tower base mortar, such as Figure 1 As shown, the following steps are included:

[0048] S1: Plasma modified composite cement

[0049] S1.1: 15 parts by weight of ultrafine silicate cement and 15 parts by weight of sulphoaluminate cement are mixed in a mixer, and then 0.03 parts by weight of hydroxypropyl methylcellulose and 0.02 parts by weight of tributyl phosphate are added, and stirred for 25 minutes to obtain a mixture;

[0050] S1.2: Load the mixed material into a closed mixer, start the atmospheric pressure plasma treatment machine, adjust the working frequency to 20KHz, the voltage to 8kV, the voltage waveform to a sine wave, and continuously spray the plasma gas into the closed mixer from the nozzle with a nozzle diameter of 10mm. Then start the mixer with a stirring speed of 100rpm for 2 hours to obtain surface modified cement.

[0051] S2: Preparation of foamed spherical CaO·ZrO2

[0052] S2.1: 3 parts by weight of Ca(OAc)2 and 3 parts by weight of Zr(NO3)4·5H2O are placed in a container, 8 parts by weight of deionized water are added, and the mixture is stirred until the solid matter in the container is completely dissolved. Then, 20 parts by weight of anhydrous ethanol and 0.4 parts by weight of polyethylene glycol are added, and the mixture is stirred at a stirring speed of 240 rpm for 1.5 hours. The mixture is then placed in a constant temperature water bath and heated at 75°C for 2 hours. The mixture is centrifuged and filtered to obtain a gel precipitate.

[0053] S2.2 Place the gel precipitate in a blender, slowly add ammonia water while stirring at a speed of 100 rpm, and add it within 1 hour to make the pH value 9. After standing for 8 hours, rinse it with deionized water until it is neutral, and then soak it in anhydrous ethanol. After refluxing for 1 hour, take it out and wash it to obtain CaO·ZrO2 prepolymer;

[0054] S2.3: Place the CaO·ZrO2 prepolymer in a vacuum drying oven and dry it at 75°C for 6 hours, then place it in a ball mill with 0.08 weight parts of TiH2 and ball mill it at 300rpm for 1 hour to obtain a CaO·ZrO2 foamed embryo. Place the CaO·ZrO2 foamed embryo in a high-temperature sintering furnace and evacuate the pressure in the furnace to 100Pa, then introduce argon until the furnace returns to normal pressure, heat it to 800°C at a heating rate of 6°C / min, keep it warm for 2 hours, then heat it to 1200°C at a heating rate of 10°C / min, keep it warm for 3 hours, then cool it naturally to room temperature with the furnace to obtain foamed spherical pore CaO·ZrO2.

[0055] S3: Composite of surface modified cement

[0056] S3.1: 30 parts by weight of surface-modified cement and 6 parts by weight of foamed spherical-pore CaO·ZrO2 are added to 20 parts by weight of quartz sand in sequence, and stirred evenly to obtain a matrix mixture;

[0057] S3.2: Add 3 parts by weight of fly ash, 0.05 parts by weight of polycarboxylic acid powder water reducer, 0.4 parts by weight of calcium formate, 2 parts by weight of calcium carbonate stone powder and 3 parts by weight of calcium sulphoaluminate expansion agent to the base mixture, stir evenly to obtain a composite wind power tower base mortar dry powder;

[0058] S3.3: When in use, mix the dry powder of the composite wind turbine tower base mortar with 14 parts of water to obtain the composite wind turbine tower base mortar for construction.

[0059] Example 3

[0060] A method for preparing a composite wind power tower base mortar, such as Figure 1 As shown, the following steps are included:

[0061] S1: Plasma modified composite cement

[0062] S1.1: 10 parts by weight of ultrafine silicate cement and 10 parts by weight of sulphoaluminate cement are mixed in a mixer, and then 0.02 parts by weight of hydroxypropyl methylcellulose and 0.01 parts by weight of tributyl phosphate are added, and stirred for 30 minutes to obtain a mixture;

[0063] S1.2: Load the mixed material into a closed mixer, start the atmospheric pressure plasma treatment machine, adjust the operating frequency to 25KHz, the voltage to 10kV, the voltage waveform to a sine wave, and continuously spray the plasma gas into the closed mixer from the nozzle, the nozzle diameter is 12mm, and then start the mixer with a stirring speed of 120rpm for 3 hours to obtain surface modified cement.

[0064] S2: Preparation of foamed spherical CaO·ZrO2

[0065] S2.1: 2 parts by weight of Ca(OAc)2 and 2 parts by weight of Zr(NO3)4·5H2O are placed in a container, 6 parts by weight of deionized water are added, and the mixture is stirred until the solid matter in the container is completely dissolved. Then, 18 parts by weight of anhydrous ethanol and 0.3 parts by weight of polyethylene glycol are added, and the mixture is stirred at a stirring speed of 300 rpm for 2 hours. The mixture is then placed in a constant temperature water bath and heated at 80°C for 3 hours. After centrifugation, the mixture is filtered to obtain a gel precipitate.

[0066] S2.2 Place the gel precipitate in a blender, slowly add ammonia water while stirring at a speed of 120 rpm, and add it within 1.5 hours to make the pH value 10. Let it stand for 12 hours, then rinse it with deionized water until it is neutral, and then soak it in anhydrous ethanol. After refluxing for 1.5 hours, take it out and wash it to obtain CaO·ZrO2 prepolymer;

[0067] S2.3: Place the CaO·ZrO2 prepolymer in a vacuum drying oven and dry it at 80°C for 8 hours, then place it in a ball mill with 0.08 weight parts of TiH2 and ball mill it at 350rpm for 1.5 hours to obtain a CaO·ZrO2 foamed embryo. Place the CaO·ZrO2 foamed embryo in a high-temperature sintering furnace and evacuate the pressure in the furnace to 600Pa, then introduce argon until the furnace returns to normal pressure, heat it to 1000°C at a heating rate of 8°C / min, keep it warm for 3 hours, then heat it to 1400°C at a heating rate of 15°C / min, keep it warm for 4 hours, then cool it naturally to room temperature with the furnace to obtain foamed spherical pore CaO·ZrO2.

[0068] S3: Composite of surface modified cement

[0069] S3.1: 20 parts by weight of surface-modified cement and 4 parts by weight of foamed spherical-pore CaO·ZrO2 are added to 15 parts by weight of quartz sand in sequence, and the mixture is stirred evenly to obtain a matrix mixture;

[0070] S3.2: Add 2 parts by weight of fly ash, 0.04 parts by weight of polycarboxylic acid powder water reducer, 0.3 parts by weight of calcium formate, 1 part by weight of calcium carbonate stone powder and 2 parts by weight of calcium sulphoaluminate expansion agent to the base mixture, stir evenly to obtain a composite wind power tower base mortar dry powder;

[0071] S3.3: When in use, mix the dry powder of the composite wind turbine tower base mortar with 10 parts of water to obtain the composite wind turbine tower base mortar for construction.

[0072] Comparative Example 1

[0073] Compared with Example 1, the difference of Comparative Example 1 is that step S1.2 is removed in Comparative Example 1, and the surface modified cement is replaced with the mixed material in the subsequent steps. The remaining steps are the same as those in Example 1, and the prepared composite wind turbine tower base mortar is recorded as Comparative Example 1.

[0074] Comparative Example 2

[0075] Compared with Example 1, the difference of Comparative Example 2 is that step S2 is removed in Comparative Example 2, and foamed spherical pore CaO·ZrO2 is not added in step S3.1. The remaining steps are the same as those in Example 1. The prepared composite wind tower base mortar is recorded as Comparative Example 2.

[0076] Three portions of the composite wind tower base mortar prepared in the embodiment, comparative example 1 and comparative example 2 of the same mass were taken respectively, and the initial fluidity of the composite wind tower base mortar prepared in the embodiment and comparative example 1 was tested at -20°C, and the compressive strength of the composite wind tower base mortar prepared in the embodiment, comparative example 1 and comparative example 2 was tested after molding and curing. The curing conditions were curing in an environment of -20°C for 7 days, and then curing at standard room temperature for 21 days. The performance test results are shown in Tables 1 and 2. It can be seen that the initial fluidity of the composite wind tower base mortar prepared in the embodiment is greater than that of comparative example 1 and comparative example 2, and the compressive strength is also greater than that of comparative example 1 and comparative example 2;

[0077] Table 1: Initial fluidity of composite wind tower base mortar

[0078]

[0079] Table 2: Compressive strength of composite wind tower base mortar

[0080] Compressive strength / MPa The first Second copy The third Example 1 102.6 103.3 102.9 Example 2 105.6 108.4 107.1 Example 3 100.3 101.4 100.5 Comparative Example 1 63.5 64.1 63.2 Comparative Example 2 26.2 25.8 26.7

[0081] It can be seen from the data of the embodiments and comparative example 1 in Table 1 and Table 2 that when the cement is not treated with deionizer in comparative example 1, the initial fluidity and compressive strength of the composite wind tower frame mortar mortar are both reduced, proving that plasma treatment can improve the initial fluidity and density of the composite wind tower frame mortar mortar, thereby improving the compressive strength of the composite wind tower frame mortar mortar;

[0082] It can also be seen from the data of Example 2 and Comparative Example 2 that when the foamed spherical pore CaO·ZrO2 is not prepared and the spherical pore mortar is added, the compressive strength of the composite wind tower mortar is significantly reduced, which proves that the preparation of foamed spherical pore CaO·ZrO2 can improve the overall compressive strength of the copper-aluminum electroplated composite tape and maintain stable hardening.

[0083] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing a composite wind power tower base mortar, characterized in that: The following steps are involved: S1: Plasma modified composite cement Mixing ultrafine silicate cement and sulphoaluminate cement in a mixer, adding a water retaining agent and a defoaming agent, stirring to obtain a mixed material, charging the mixed material into a closed mixer, starting a normal pressure plasma treatment machine to spray plasma gas into the closed mixer, performing plasma treatment while stirring, and obtaining surface modified cement; S2: Preparation of foamed spherical CaO·ZrO2 Ca(OAc)2 and Zr(NO3)4·5H2O are dissolved in deionized water, and then anhydrous ethanol and a dispersant are added, and the mixture is heated in a constant temperature water bath after stirring, and filtered after centrifugation to obtain a gel precipitate, and ammonia water is slowly added dropwise to the gel precipitate while stirring, and the mixture is allowed to stand and then immersed in anhydrous ethanol for reflux, and washed to obtain a CaO·ZrO2 prepolymer, and the CaO·ZrO2 prepolymer is dried and ball-milled with a foaming agent, and then sintered to obtain foamed spherical porous CaO·ZrO2; S3: Composite of surface modified cement Surface modified cement and foamed spherical pore CaO·ZrO2 are sequentially added to quartz sand, stirred evenly to obtain a matrix mixture, fly ash, water reducing agent, antifreeze early strength agent, calcium carbonate stone powder and expansion agent are added to the matrix mixture, stirred evenly to obtain a composite wind power tower base mortar dry powder material, and when used, the composite wind power tower base mortar dry powder material is mixed with water to obtain a composite wind power tower base mortar for construction.

2. The method for preparing a composite wind power tower base mortar according to claim 1, characterized in that: Step S1 plasma modified composite cement comprises the following steps: S1.1: 10-15 parts by weight of ultrafine silicate cement and 10-15 parts by weight of sulphoaluminate cement are mixed in a mixer, and then 0.02-0.03 parts by weight of a water retaining agent and 0.01-0.02 parts by weight of a defoaming agent are added, and stirred for 25-30 minutes to obtain a mixed material; S1.2: Load the mixed material into a closed mixer and start the atmospheric pressure plasma treatment machine, adjust the operating frequency to 20-25KHz, the voltage to 8-10kV, the voltage waveform to a sine wave, continuously spray the plasma gas into the closed mixer from the nozzle, and then start the mixer with a stirring speed of 100-120rpm for 2-3 hours to obtain surface modified cement.

3. The method for preparing a composite wind power tower base mortar according to claim 1, characterized in that: Step S2 Preparation of foamed spherical CaO·ZrO2, comprising the following steps: S2.1: 2-3 parts by weight of Ca(OAc)2 and 2-3 parts by weight of Zr(NO3)4·5H2O are placed in a container, 6-8 parts by weight of deionized water are added, and the mixture is stirred until the solid matter in the container is completely dissolved, and then 18-20 parts by weight of anhydrous ethanol and 0.3-0.4 parts by weight of a dispersant are added, and the mixture is stirred at a stirring speed of 240-300 rpm for 1.5-2 hours, and then the mixture is placed in a constant temperature water bath and heated at a temperature of 75-80°C for 2-3 hours, and then centrifuged and filtered to obtain a gel precipitate; S2.2 Place the gel precipitate in a blender, slowly drop ammonia water while stirring at a stirring speed of 100-120 rpm, let it stand for 8-12 hours, then rinse it with deionized water until it is neutral, and then soak it in anhydrous ethanol, reflux for 1-1.5 hours, then take it out and wash it to obtain a CaO·ZrO2 prepolymer; S2.3: Place the CaO·ZrO2 prepolymer in a vacuum drying oven and dry it at a temperature of 75-80℃ for 6-8 hours, then place it in a ball mill with 0.06-0.08 weight parts of foaming agent and ball mill it at a speed of 300-350rpm for 1-1.5 hours to obtain a CaO·ZrO2 foamed embryo, place the CaO·ZrO2 foamed embryo in a high-temperature sintering furnace and evacuate the pressure in the furnace to 100-600Pa, then introduce argon until the furnace returns to normal pressure, heat it to 800-1000℃ at a heating rate of 6-8℃ / min, keep it warm for 2-3 hours, then heat it to 1200-1400℃ at a heating rate of 10-15℃ / min, keep it warm for 3-4 hours, then cool it naturally to room temperature with the furnace to obtain foamed spherical pore CaO·ZrO2.

4. The method for preparing a composite wind power tower base mortar according to claim 1, characterized in that: Step S3: Compounding of surface modified cement, comprising the following steps: S3.1: Add 20-30 parts by weight of surface-modified cement and 4-6 parts by weight of foamed spherical-pore CaO·ZrO2 to 15-20 parts by weight of quartz sand, and continue to stir evenly to obtain a matrix mixture; S3.2: Add 2-3 parts by weight of fly ash, 0.04-0.05 parts by weight of water reducing agent, 0.3-0.4 parts by weight of antifreeze early strength agent, 1-2 parts by weight of calcium carbonate stone powder and 2-3 parts by weight of expansion agent to the base mixture, stir evenly to obtain a composite wind power tower base mortar dry powder; S3.3: When using, mix the dry powder with 10-14 parts of water to obtain a composite wind power tower base mortar for construction.

5. The method for preparing a composite wind power tower base mortar according to claim 2, characterized in that: The nozzle diameter in step S1.2 is 10-12 mm.

6. The method for preparing a composite wind power tower base mortar according to claim 3, characterized in that: The dispersant in step S2.1 is polyethylene glycol.

7. The method for preparing a composite wind power tower base mortar according to claim 3, characterized in that: In step S2.2, the ammonia water is added dropwise at a speed such that the pH value is 9-10 within 1-1.5 hours.

8. The method for preparing a composite wind power tower base mortar according to claim 3, characterized in that: The blowing agent in step S2.3 is TiH2.

9. The method for preparing a composite wind power tower base mortar according to claim 4, characterized in that: The water reducing agent in step S3.2 is a polycarboxylic acid powder water reducing agent, the antifreeze and early strength agent is calcium formate, and the expansion agent is a calcium sulfoaluminate expansion agent.

Citation Information

Patent Citations

  • Bridge bearing mortar and production method thereof

    CN104370511A

  • Low-temperature type base sizing agent and use method thereof

    CN114853436A